THE PHENOMENON OF TRANSFER PRICING IN MANUFACTURING COMPANIES IN INDONESIA - Oktafiana, Ista Ayu; Najihah, Naila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2026)
Transfer pricing has become a strategic issue at the intersection of accounting, international taxation, and development policy because it is directly related to the stability of state revenue and tax fairness. Therefore, this study aims to examine the effect of profitability, exchange rates, and foreign ownership on transfer pricing. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. The sample was determined using purposive sampling. The number of samples obtained in accordance with the criteria was 22 manufacturing companies with 66 annual reports. All data will be processed using multiple linear regression analysis. The results of the study indicate that profitability has a positive effect on transfer pricing, meaning that high profitability enables companies to implement transfer pricing through the process of profit shifting. Exchange rates and foreign ownership do not affect transfer pricing, meaning that exchange rates are not taken into consideration in implementing transfer pricing, and high foreign ownership makes it possible to suppress transfer pricing practices in order to pay attention to future risks and a decline in company value that will affect minority and majority shareholders. The results of this study have implications for strengthening agency theories, namely that owners (especially foreign owners) and managers can utilize transfer pricing to shift profits across entities within a group.